Pengaruh Disiplin Kerja, Budaya Organisasi dan Etika Kerja terhadap Kinerja Karyawan PT Amaze Indonesia Jaya - Silvi Aprilia Waluyo; Rike Kusuma Wardhani; Suseno Hendratmoko (Lokawati : Jurnal Penelitian Manajemen dan Inovasi Riset, 2025)
This study aims to examine and analyze the influence of work discipline, organizational culture, and work ethics on employee performance at PT Amaze Indonesia Jaya. The background of this study is based on the importance of human resources as a company's main asset, where the level of discipline, established work culture, and applied work ethics can influence employee performance achievement. This study uses a quantitative approach by utilizing primary data obtained through questionnaires and secondary data obtained from company documents. The study population is all employees of PT Amaze Indonesia Jaya, with a total of 50 people who are also used as research samples using saturated sampling techniques. The research instrument has been tested for validity and reliability to ensure the feasibility of the collected data. Data analysis was carried out through validity tests, reliability tests, classical assumption tests, multiple linear regression analysis, and hypothesis testing using t-tests and F-tests. The results of the study indicate that partially, work discipline has a positive and significant effect on employee performance, which means that the higher the discipline, the better the performance produced. Organizational culture has also been proven to have a positive and significant effect on employee performance, indicating that the values, norms, and habits that apply in the organization can motivate employees to work more optimally. Furthermore, work ethics has a positive and significant impact on performance, indicating that employee integrity, responsibility, and professionalism contribute to the achievement of work targets. Simultaneously, the F-test results indicate that work discipline, organizational culture, and work ethics collectively have a significant impact on employee performance.